ANALYSIS OF FLOOD DISASTER POTENTIAL IN THE SAUKOREM AREA, AMBERBAKEN REGENCY, TAMBRAUW REGENCY, SOUTHWEST PAPUA PROVINCE: ANALISIS POTENSI BENCANA BANJIR DI DAERAH SAUKOREM DISTRIK AMBERBAKEN KABUPATEN TAMBRAUW PROVINSI PAPUA BARAT DAYA - warijo, alfons; Mayzarah, Erikha M. (INTAN Jurnal Penelitian Tambang, 2024)
Floods are hydrometeorological disasters that frequently occur in Southwest Papua Province, including Tambrauw Regency.  This research was conducted in January – July 2024 in Saukorem Village, Tambrauw Regency, West Papua Province. The research area is located at the coordinates 0° 34' 00" South Latitude - 133° 12' 00" East Longitude. This research employed the overlay method with weighting and scoring based on several key parameters such as distance from the river, land use, type of lithology, altitude, slope, and rainfall. The result reveals that the highest flood potential covers an area of 220,9 ha (hectares) or 2,8% of the total area. Moderate flood potential has 683 ha (hectares) representing 8,7% area, while the low flood area accounts for 1202.6 ha (hectares) or 15,3%. Area with negligible potential for flooding covering 4930.5 ha (hectares) with a percentage of 62,8%, followed by areas with no flood potential which cover 811.1 ha (hectares) or 10,4%.